PENANGGALAN BUGIS-MAKASSAR DALAM PENENTUAN AWAL BULAN KAMARIAH MENURUT SYARIâAH DAN SAINS - Yusmar, Syarifuddin (Hunafa: Jurnal Studia Islamika, 2008)
The Bugisi and the Makassarese are two great ethnics living in South Sulawesi. The Bugisi and the Makassarese are two different ethnics, but they have similar culture, particularly in the sight ofÂ  the written language. The two ethnics employ lontara alphabets in preaching religion, engaging commerse, doing farming, and calculating timeÂ Â  (date calculation) called pananrang (guide to all daily activities). The Pananrangs among the Bugisi and the Makassarese among others are pnR aEso (Pananrang Esso [guide to day calculation]), (2) pnR aulE (Pananrang Uleng [guide to month calculation]), and (3) pnR tau (Pananrang Taun [guide to year calculation] ).Kata Kunci:Â Â Â  pananrang esso, pananrang uleng, panarang taun penanggalan Bugis-Makassar, syariâah, sains